Prison health care in the Czech Republic, Hungary and Poland - MacDonald, Morag (HEUNI papers, 2001)
This study of health care in Central European penal systems was commissioned by HEUNI and took place during January and February, 2001. The three countries included in the research were the Czech Republic, Hungary and Poland. These countries were selected to complement the work already done by Roy Walmsley (1996) and his current follow-up study of the prison systems as a whole in Central and Eastern European countries. The link with Roy Walmsley’s research was important as a means of securing access to appropriate key personnel in each of the countries and as a means of securing general information about the prison systems. This study also complements the work already carried out in Italy and England and Wales about the structure and key issues facing the two prison systems in the areas of health policy and more specifically on HIV and drugs policy (MacDonald, 1999.)The purpose of the visits to the Czech Republic, Hungary and Poland was to prepare a report that provides descriptive data about the current health policies in prisons in the countries visited. Interviews were to be carried out with key officials in each of the countries to discover the extent to which international standards are currently adhered to in the implementation of health policy; the reasons for any lack of adherence; the concerns expressed, and the state of progress. It is the intention to return to each of these countries to undertake a more indepth follow-up study in the area of implementation of health policy in the form of audits in a sample of prisons, which will also include interviews with prisoners. Although this report is primarily concerned with the provision of health care services in each of the three countries’ prison services it is also recognised that there are other factors that make a significant contribution to the health of prisoners. Therefore, a variety of issues (overcrowding, budget constraints, drugs and sex in prison and so on) have been included in the report in so far as they impact on prisoner health. Three days were spent in each country. Interviews were carried out with a range of key officials in the prison service administration. At least one prison was visited in each country and further interviews were undertaken with the prison governor and medical staff working in the prison hospital/ department.